Identification Of A Comprehensive Healthy School Model In The Prevention Of Diarrheal Disease In Elementary Schools - Hidayati, Fajrina; Rahmat, Andree; Solida, Adila; Wisudariani, Evy (LPPM Universitas Prima Nusantara Bukittinggi, 2024)
Diarrhea is a disease that is often suffered by children and toddlers, where one of the factors is influenced by the environment and hygiene behavior. The incidence of diarrhea in Jambi City has increased every year, so it is necessary to identify the implementation of the Comprehensive Health School Model (CHSM). Identifying the implementation of CHSM can help identify how the implementation of diarrhea prevention in schools. The purpose of this study was to identify the implementation of CHSM for the prevention of diarrhea in elementary schools in Jambi City. This research is a descriptive observational study. The samples in this study were 13 public elementary schools in Jambi City. The results of the study from 3 CHSM assessment criteria, it is known that the physical environment criteria (clean water facilities meet the requirements (69.2%), latrine facilities on average meet the requirements (69.2%), most of the primary schools waste water disposal facilities do not meet the requirements (76.1%), and most of the waste disposal facilities meet the requirements (92.3%)), teaching and learning criteria more than half of primary schools (53.8%) are appropriate and implement teaching and learning about healthy schools, sanitation and clean and healthy living behavior in schools, school policy criteria are known that most schools already have and implement policies on healthy schools. The principal in a school has a very important role and responsibility in managing the school in terms of academic and non-academic matters, especially in providing maintenance on school sanitation facilities. Sanitation management involves all school members and related parties, such as committee members, parents of students, and other interested parties. Good sanitation management improves the school community's ability to utilize a clean, healthy and beautiful school environment.